Possible risks of using medications for obesity (Research, Society and Development, 2023)
The increase in the use of weight loss medications reflects the pursuit of quick results but carries significant risks. From appetite suppressants to fat absorption inhibitors, these options promise immediate efficacy but often lead to adverse effects such as insomnia, irritability, increased blood pressure, and nausea. Many of these medications are banned in several countries due to the health issues they can cause, including cardiac issues, depression, and even the risk of death. The research is based on 19 carefully selected bibliographic studies out of 61 that were analyzed. The results highlight the dangers associated with weight loss medications such as sibutramine, femproporex, orlistate, phentermine, fenfluramine, dexfenfluramine, GLP-1 receptor agonists (liraglutide, semaglutide), and the combination of bupropion with naltrexone. The study aims to raise awareness about the dangers of these medications, emphasizing the importance of detailed patient information regarding risks, benefits, side effects, and off-label use. In this way, it promotes a more holistic understanding of weight loss, highlighting the need for professional guidance and healthy choices.